The epidemiology of supernumerary teeth and the associated molecular mechanism. (3rd July 2017) - Lu, Xi; Yu, Fang; Liu, Junjun; Cai, Wenping; Zhao, Yumei; Zhao, Shouliang; Liu, Shangfeng
ABSTRACT: Supernumerary teeth are common clinical dental anomalies. Although various studies have provided abundant information regarding genes and signaling pathways involved in tooth morphogenesis, which include Wnt, FGF, BMP, and Shh, the molecular mechanism of tooth formation, especially for supernumerary teeth, is still unclear. In the population, some cases of supernumerary teeth are sporadic, while others are syndrome-related with familial hereditary. The prompt and accurate diagnosis of syndrome related supernumerary teeth is quite important for some distinctive disorders. Mice are the most commonly used model system for investigating supernumerary teeth. The upregulation of Wnt and Shh signaling in the dental epithelium results in the formation of multiple supernumerary teeth in mice. Understanding the molecular mechanism of supernumerary teeth is also a component of understanding tooth formation in general and provides clinical guidance for early diagnosis and treatment in the future.